2013
DOI: 10.1186/1746-6148-9-221
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of equine multipotent mesenchymal stromal cells by enzymatic tissue digestion or explant technique: comparison of cellular properties

Abstract: BackgroundThe treatment of tendon lesions with multipotent mesenchymal stromal cells (MSCs) is widely used in equine medicine. Cell sources of MSCs include bone marrow, as well as solid tissues such as adipose tissue. MSCs can be isolated from these solid tissues either by enzymatic digestion or by explant technique. However, the different preparation techniques may potentially influence the properties of the isolated MSCs. Therefore, the aim of this study was to investigate and compare the effects of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 60 publications
6
39
2
Order By: Relevance
“…Investigative results confirm undifferentiated cell migration in vitro and in vivo . Cell migration from spheroids generated with passage 3 MSCs from adipose tissue, superficial digital flexor tendon and umbilical cord matrix was measured after 24 h of spheroid culture in standard culture medium on adherent cultureware .…”
Section: Cell Migrationmentioning
confidence: 70%
See 2 more Smart Citations
“…Investigative results confirm undifferentiated cell migration in vitro and in vivo . Cell migration from spheroids generated with passage 3 MSCs from adipose tissue, superficial digital flexor tendon and umbilical cord matrix was measured after 24 h of spheroid culture in standard culture medium on adherent cultureware .…”
Section: Cell Migrationmentioning
confidence: 70%
“…Explant isolation, the process of MSC migration from minced tissue in ideal culture conditions, was proposed to reduce the potential effects of tissue digestion on the cells. Collagenase digestion of equine adipose tissue, tendon and umbilical cord matrix resulted in higher MSC yield from all tissues than from explant isolation, and there were no differences in cell proliferation or differentiation characteristics between the techniques . Future work to optimise cell isolation that includes determination of cell phenotype will be important to elucidate the effects of gradients, digestion and associated protocols on cells.…”
Section: Isolation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic digestion with consequent mechanical damage during centrifugation times seems as a laborious procedure that may lead to reduced cell viability (31). It has been indicated that the characteristics of isolated cells may be altered by the use of enzymatic digestion method as a repercussion of different environment of the cells (32). In explant culture method, the processing time for the tissue is faster than conventional enzymatic method.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups reported success in isolating and establishing MSCs cultures from UCM in human [2]–[8] as well as in large animal models, such as horses [9]–[16], pigs [17], [18], and dogs [19]–[22].…”
Section: Introductionmentioning
confidence: 99%